2004
DOI: 10.1113/expphysiol.2004.027946
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic responses following intermittent supramaximal exercise in athletes

Abstract: We aimed to investigate haemodynamics during active and passive recovery following repeated bouts of supramaximal exercise. Seven male athletes underwent two sessions of supramaximal exercise which consisted of a warm-up and of five bouts of cycling at the maximum speed possible for 30 s against a resistance equivalent to 150% of the maximum workload achieved in a previous incremental test. Bouts were separated by 1 min of recovery and followed by 10 min of recovery which was either active (pedalling at 40 W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 29 publications
(63 reference statements)
8
36
0
2
Order By: Relevance
“…The main concern with this method, during exercise, is that respiration and muscle contractions generate artefacts that render the reference points of impedance waveforms unrecognizable, thus rendering SV assessment unreliable. In our laboratory, we have developed a procedure for processing impedance signals during exercise which, as previously reported (Crisafulli et al 2003b(Crisafulli et al , 2004(Crisafulli et al , 2006(Crisafulli et al , 2007(Crisafulli et al , 2008, separates impedance traces from artefacts by visual inspection of recorded signals by a skilled operator. However, in the present study, we were unable to gather a suYcient number of reliable impedance waveforms during the arm cranking sessions, as this kind of strain caused signiWcant chest movements that aVected impedance readability.…”
Section: Considerations On Sv Measurement and Limitations Of The Presmentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern with this method, during exercise, is that respiration and muscle contractions generate artefacts that render the reference points of impedance waveforms unrecognizable, thus rendering SV assessment unreliable. In our laboratory, we have developed a procedure for processing impedance signals during exercise which, as previously reported (Crisafulli et al 2003b(Crisafulli et al , 2004(Crisafulli et al , 2006(Crisafulli et al , 2007(Crisafulli et al , 2008, separates impedance traces from artefacts by visual inspection of recorded signals by a skilled operator. However, in the present study, we were unable to gather a suYcient number of reliable impedance waveforms during the arm cranking sessions, as this kind of strain caused signiWcant chest movements that aVected impedance readability.…”
Section: Considerations On Sv Measurement and Limitations Of The Presmentioning
confidence: 99%
“…In order to obtain reliable measurements of cardiovascular variables, we have developed a method for processing impedance data through which we eliminate traces aVected by impedance artifacts from hemodynamic calculation, thus obtaining reliable and reproducible hemodynamic estimation during exercise and recovery. This data acquisition procedure is described in detail in our previous works (Crisafulli et al 2003b(Crisafulli et al , 2004(Crisafulli et al , 2006(Crisafulli et al , 2007(Crisafulli et al , 2008. BrieXy, by means of a digital chart recorder (ADInstruments, PowerLab 8sp, Castle Hill, Australia) we stored NCCOM 3-derived analog traces of electrocardiogram, thorax impedance (Z 0 ), and Z 0 Wrst derivative.…”
Section: Assessment Of Hemodynamic Datamentioning
confidence: 99%
“…In particular, it was found that stroke volume and contractility were significantly enhanced compared with exercise not preceded by nitrate administration. This effect was similar to that which is observed in the second window of protection after exercise-induced ischaemia (Crisafulli et al, 2004a). Therefore, it could be argued that in individuals suffering from stable angina, treatment with nitric oxide donors can mimic the effect of an exerciseinduced second window of protection (Crisafulli et al, 2004b;Jneid et al, 2005).…”
mentioning
confidence: 59%
“…For ethical reasons, it is not possible to employ the same end-point in humans, thus we used haemodynamic parameters as end-points to discover any beneficial effect of nitrates administration upon cardiovascular function. Moreover, the fact that in our study healthy participants did not receive any benefit from nitroglycerin does not necessary rule out the possibility that their hearts were preconditioned against ischaemia-induced necrosis, but provides support for the concept that ischaemia must occur during the second window of protection to detect any beneficial cardiac effect (Crisafulli et al, 2004a). An improvement of endothelial function by pharmacological early preconditioning has been described in animals and humans (Gross, 2005).…”
Section: Exercise-swopmentioning
confidence: 85%
See 1 more Smart Citation